NUMERIC MODELING FOR DETERMINATION OF THE CRUSHING ZONE THICKNESS AROUND THE TUNNEL BASED ON MOHRCOULOMB AND HOEK-BROWN CRITERIA - Lumbantobing, Andrew
In underground mine design, tunneling is often done. One of the things that is the focus in making tunnels is the condition of the rock around the tunnel. The rock conditions around the tunnel affect the crushing zone that will occur in the tunnel. Therefore, it is necessary to analyze the rock properties. The analysis was carried out based on the Rock Mass Rating (RMR) classification developed by Bienawski. This study aims to analyze how large the tunnel crushing zone that can occur using RockScience 2 (RS2) software by implementing the finite element method in the analysis process. The analysis was carried out using the Mohr Coulomb criteria and the Hoek Brown criteria under both hydrostatic stress and non-hydrostatic stress conditions. The rock mass classes around the tunnel to be used are fair rock mass class and poor rock mass class. The tunnel is modeled at a depth of 500 meters with a circular shape with a diameter of 4 meters. The unit of weight used for rock is 0.027 MN/m3. The result of this study is that the crushing zone for the medium class rock mass has a smaller crushing zone value than the poor rock mass class. This difference is caused by different rock parameters in each class. Then the crushing zone that obtained using the Hoek Brown criteria is smaller than the crushing zone using the Mohr Coulomb criteria both in terms of hydrostatic stress and non-hydrostatic stress conditions. The factor that influences this difference is because Hoek Brown approaches cohesion (c) and internal friction angle (?) using the parameters mb (material constant) and s (rock mass constant), which are much smaller values.